Comprehensive Characterization of Immune Landscape Based on Epithelial-Mesenchymal Transition Signature in OSCC: Implication for Prognosis and Immunotherapy - Zhang, Si-yuan; Ren, Xian-yue; Wang, Chun-yang; Chen, Xi-juan; Cao, Ruo-yan; Liu, Qin; Pan, Xue; Zhou, Jia-ying; Zhang, Wei-lin; Tang, Xin-Ran; Cheng, Bin; Wu, Tong (Frontiers in Oncology, 2021)
Current anatomic TNM stage classification fails to capture the immune heterogeneity of oral squamous cell carcinoma (OSCC). Increasing evidence indicates the strong association between epithelial-mesenchymal transition (EMT) and tumor immune response. In this study, we employed an EMT signature to classify OSCC patients into epithelial- (E-) and mesenchymal- (M-) phenotypes using TCGA and GSE41613 transcriptome data. The ESTIMATE and CIRBERSORT analyses implied that the EMT signature genes originated from the stroma of the bulk tissue. The M-subtype tumors were characterized as “immune-hot” with more immune cell infiltration than the E-subtype ones. The low infiltration of active immune cells, the high infiltration of inactive immune cells, and the high expressions of immune checkpoints demonstrated an immunosuppressive characteristic of the M-subtype tumors. Moreover, we developed and validated a novel prognostic classifier based on the EMT score, the expressions of seven immune checkpoints, and the TNM stages, which could improve the prediction efficiency of the current clinical parameter. Together, our findings provide a better understanding of the tumor immune heterogeneity and may aid guiding immunotherapy in OSCC.